The Structure Of Consumer Finance Industry In Emerging Market (Empirical Evidence : Indonesia 2000-2015) - Suwinto Johan (Universitas Tarumanagara, 2019)
The aim of this paper is to study the structure of the Indonesia Finance Company Industry over the periode 2001-2015. The finance company industry is growing rapidly from Rp37 trillion in 2001 to Rp. 425 trillion in 2015 with a compounded annual growth rate (CAGR) of 18%. At the same time, the number company in the industry has reduced from 245 in 2001 to 203 in 2015. We use the Concentration Ratio (CR) and Herfindahl–Hirschman Index (HHI) to measure the structure of the industry. Our sample consists of 97 companies in 2001 to 125 companies to 2015. The empirical results show that Indonesia finance company industry is not highly concentrated. The HHI has reached 451 in 2015 from 313 in 2010. In fact, there is a significant increase in the concentration ratio since 2000 to 2015, especially the concentration in CR 4, CR8 and CR12. The CR4 has reached 34,12%, CR8 has reached 51,15%, CR12 61,72% and CR20 by 76,57%. The CR4 means that the top 4 finance companies has controlled 34,12% over the total productive asset of the financing industry by 2015. The CR4 has almost reached the oligopoly category. However, there is a potential of higher concentration if we group the companies by the shareholders’ ownership, due to the controlling issue of the shareholders.